Amino acid positron emission tomography to monitor chemotherapy response and predict seizure control and progression-free survival in WHO grade II gliomas. Issue 5 (17th November 2015) - Roelcke, Ulrich; Wyss, Matthias T.; Nowosielski, Martha; Rudà, Roberta; Roth, Patrick; Hofer, Silvia; Galldiks, Norbert; Crippa, Flavio; Weller, Michael; Soffietti, Riccardo
Abstract: Background: Patients with WHO grade II glioma may respond to chemotherapy that is currently not standardized regarding timing and treatment duration. Metabolic changes during chemotherapy may precede structural tumor volume reductions. We therefore compared time courses of amino acid PET and MRI responses to temozolomide (TMZ) and assessed whether responses correlated with seizure control and progression-free survival (PFS). Methods: PET and MRI were performed before and during TMZ chemotherapy. Tumor volumes were calculated using regions-of-interest analysis. Amino acid uptake was also quantified as metabolically active tumor volume and tumor-to-cerebellum uptake ratio. Results: One hundred twenty-five PET and 125 MRI scans from 33 patients were analyzed. Twenty-five patients showed metabolic responses that exhibited an exponential time course with a 25% reduction of the active volume on average after 2.3 months. MRI responses followed a linear course with a 25% reduction after 16.8 months. Reduction of metabolically active tumor volumes, but not reduction of PET uptake ratios or MRI tumor volumes, correlated with improved seizure control following chemotherapy ( P = .012). Receiver-operating-characteristic curve analysis showed that a decrease of the active tumor volume of ≥80.5% predicts a PFS of ≥60 months ( P = .018) and a decrease of ≥64.5% a PFS of ≥48 months ( P = .037). Conclusions: Amino acid PET is superior to MRI for evaluating TMZ responses in WHO grade II glioma patients. The response delay between both imaging modalities favors amino acid PET for individually tailoring the duration of chemotherapy. Additional studies should investigate whether this personalized approach is appropriate with regard to outcome.